Integrating the Microbiome Into Infection Ecology and Evolution in Wild Animals - Jingdi Li; Ian Will; Luís M. Silva; Tommy J. Travers‐Cook; Paradyse E. Blackwood; Kayla C. King (Molecular Ecology, 2026)
Parasites are a ubiquitous force in nature threatening wildlife populations and ecosystems. Interactions between hosts and their parasites are impacted by host‐associated microbiomes, which are essential for host development, physiology and immunity. We synthesise current understanding of the ecological interactions between host microbiomes and parasites, ranging from competitive to facilitative, and explore their potential evolutionary consequences for parasite virulence and transmission in the wild. We highlight recent mechanistic insights that support integrating a microbiome perspective into wildlife parasitology, with examples across diverse animal taxa including amphibians, bats, insects and corals, particularly within the context of climate change. Adopting such a holistic approach can open new avenues whereby host microbial shifts can be used to predict and mitigate infectious diseases in wild populations. Finally, we propose a conceptual framework to guide future research on microbiome‐parasite–host interactions, aiming to better reflect natural ecological complexities and advance both fundamental understanding and conservation applications.